Cultural Intelligence and Hybrid Work: Implications for Global Team Management - Deni Surapto (Al-Makki Publisher, 2025)
The post-pandemic development of hybrid work has changed the way global organizations manage cross-border teams. This work model presents opportunities for flexibility, but it also poses challenges of coordination, technostress, and intercultural miscommunication. In this context, cultural intelligence (CQ) is an important competency to maintain the effectiveness of global team collaboration. This study aims to analyze the influence of the four dimensions of CQ on the performance of hybrid global teams, examine the role of communication norms as mediators, and assess the moderation effect of hybrid work design and technostress. The research uses a quantitative approach with an explanatory design. Data was obtained through an online survey of 245 respondents working on hybrid global teams in Southeast Asia. The analysis was conducted with SEM-PLS to test direct relationships, mediation, and moderation, and fsQCA to explore the configuration of factors that affect team performance. The findings show that all dimensions of CQ have a positive effect on performance, with motivational CQ (B = 0.41) and behavioral CQ (B = 0.36) as the main predictors. Communication norms have been shown to mediate the CQ–performance relationship, while the hybrid design of the 3–2 pattern reinforces the influence. Technostresses act as a negative moderator that weakens the impact of CQ. Configuration analysis revealed that a combination of high CQ, clear communication norms, structured hybrid design, and low technostress are optimal conditions for improving team performance and retention. This research confirms the need for organizations to integrate CQ training, hybrid communication regulations, and a balanced hybrid work design to ensure the effectiveness and well-being of global teams.